Music Theory in the Public Sphere. The Case of Hermann von Helmholtz - Benjamin Steege (Zeitschrift der Gesellschaft für Musiktheorie)
The musical writings of Hermann von Helmholtz are often read as the epitome of a high-technical sophistication enabled by intense investment in German experimental science after 1850. But an overlooked, contrasting aspect of these texts’ historical significance should be acknowledged: namely their intended status as popular science. Helmholtz’s attempt to ground modern harmonic practice in the empirical ‘sensations of tone’ was arguably the first (and conceivably the last) work of such ambitious scope that was explicitly aimed not merely at an elite musical community, but at a wider public. This article explores the implications of a historical popular-scientific agenda for music theory and proposes that music theory’s popularization effectively altered its very object.